Mobile robot safe navigation in unknown environment - Shayestegan, Mohsen; Marhaban, Mohammad Hamiruce (IEEE, 2012)
This paper provides a mobile robot navigation strategy using fuzzy logic is developed for a two wheeled mobile robot in a static environment. The information about the target and the low-range sensory information are used by the controller to produce the commands that gives a favorable direction in terms of reaching to the target within the collision detection. Furthermore, the mobile robot does not suffer from typical ushape environment by a planned local minimum trapping algorithm and also designed controller is easy to understand, simple, and not sensitive to the system model parameters. The resulting path, connecting a start point to a target position where in this method there is no information about the environment. Due to its ability and effortlessness for real-time implementation, fuzzy controller has been used for the proposed navigation strategy. The resulting navigation system is implemented on the e-puck robot in Webots software, and tested in several environments. Simulation results are presented which show the effectiveness of the proposed fuzzy controller and local minimum algorithm to safely navigate the mobile robot in various dead end trap environment.